Generalized poroelasticity framework for micro‐inhomogeneous rocks. (13th June 2016) - Müller, Tobias M.; Sahay, Pratap N.
ABSTRACT: Poroelastic modelling of micro‐inhomogeneous rocks is of interest for applications in rock physics and geomechanics. Laboratory measurements from both communities indicate that the Biot poroelasticity framework is not adequate. For the case of a macroscopically homogeneous and isotropic rock, we present the most general poroelasticity framework within the scope of equilibrium thermodynamics that is able to capture the effects of micro‐inhomogeneities in a natural way. Within this generalized poroelasticity framework, the concept of micro‐inhomogeneity is generically related to partial localization of the deformational potential energy either in the solid phase, including the interfacial region or in the fluid phase. The former case can occur in the presence of surface roughness or multi‐mineralic frame and the latter case can be related to suspended particles residing in the fluid phase. A measure for micro‐inhomogeneity is the coefficient that governs the effective pressure dependence of porosity changes as described by the porosity perturbation equation of this framework. It can be therefore equivalently interpreted as porosity effective pressure coefficient or as micro‐inhomogeneity parameter. We show how this parameter and the other poroelastic constants embedded in this framework can be expressed in terms of experimentally accessible poroelastic constants.